العلاقة بين القدرة على القراءة العربية الصحيحة والقدرة على القواعد النحوية لطلبة السنة الثالثة بمدرسة بحر العلوم للمعلمين و المعلمات نظام ست سنوات تامبأ براس جومبانج - Syafi'i, Ikhsan Rizal (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2017)
The purpose of this research is to explain about tawābi ’and find out the learning methods that are suitable for middle-level students and their application. And with this research is expected to expand the knowledge of educators and students in the field of science, especially in the chapter at-tawābi 'and the appropriate learning methods. And this type of research is library research using various books. Then all explanations by reading books related to the research title. And the researcher used the Wasfi method in this study, this research begins with an explanation of at-tawābi 'and its types and laws, from the explanation it can be concluded that the learning method that is suitable for the middle-level students and their application is based on the books in accordance with research. The results of this study are that there are 4 parts at-tawābi ’: anna’t, attaukîd, al‘ atf, and al badal. Anna’t consists of two types: anna’tussababiy and anna’tulhaqiqiy, attaukîd there are two types: lafżiy and ma’nawiy. Whereas al'aṭf consists of two parts: ‘aṭful bayān and‘ atfunnasaq (‘aṭfun bil hurûf). The letters ‘aṭf have nine: waw, fa ', śumma, aw, hatta, am, lakin, bal, and lā. Whereas the Badal consists of four parts: albadal almuṭãbiq, badalu ba'din min kullin, badalul isytimāl, albadal almubayyin lil mubdal minhu. And the learning method that is suitable for middle-level students is the inductive method, because the learning process is fast starting with mentioning vocabulary examples then an example explanation by discussing with students then drawing conclusions / rules from students with the help of the teacher. And the application with five parts: opening, giving examples, comparison, drawing conclusions and training.